2022
DOI: 10.1038/s41598-022-18243-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lidocaine on hemodynamic and respiratory parameters during laparoscopic appendectomy in children

Abstract: We assessed the influence of systemic lidocaine administration on ventilatory and circulatory parameters, and the pneumoperitoneum impact on the cardiopulmonary system during a laparoscopic appendectomy in children. A single-center parallel single-masked randomized controlled study was carried out with 58 patients (3–17 years). Intravenous lidocaine bolus of 1.5 mg/kg over 5 min before induction of anesthesia followed by lidocaine infusion at 1.5 mg/kg/h intraoperatively. Respiratory system compliance (C, C/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The results showed that the RG had evidently shorter time to loss of eyelash reflex, pain resolution, and recovery from anesthesia than the CG, suggesting that ATR + REMI can establish a good anesthetic effect in pediatric AA surgery. The major AEs observed after AA surgery in children were respiratory depression, hypoxemia, bradycardia, nausea and vomiting, and hypotension, similar to the results reported by Kaszyński et al [ 20 ]. RG had a lower overall incidence of AEs than CG, indicating the increased benefit conferred by ATR + REMI, thereby preventing postoperative AEs in pediatric patients undergoing surgery for AA.…”
Section: Discussionsupporting
confidence: 87%
“…The results showed that the RG had evidently shorter time to loss of eyelash reflex, pain resolution, and recovery from anesthesia than the CG, suggesting that ATR + REMI can establish a good anesthetic effect in pediatric AA surgery. The major AEs observed after AA surgery in children were respiratory depression, hypoxemia, bradycardia, nausea and vomiting, and hypotension, similar to the results reported by Kaszyński et al [ 20 ]. RG had a lower overall incidence of AEs than CG, indicating the increased benefit conferred by ATR + REMI, thereby preventing postoperative AEs in pediatric patients undergoing surgery for AA.…”
Section: Discussionsupporting
confidence: 87%
“…Depue et al showed that the combined treatment of 0.25 to 0.5 mg/kg of preoperative IV lidocaine with propofol infusion did not significantly affect the pain and distress of 2 - 7 years old patients and the distress of their parents and physicians during the procedure ( 42 ). In another study of children aged 3 - 17, lidocaine infusion during laparoscopic appendectomy did not improve circulatory and respiratory alterations during pneumoperitoneum ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Forster et al evaluated 40 adults and showed that IV lidocaine in combination with ketamine and propofol for colonoscopy reduced the required doses of propofol ( 34 ). Although preoperative administration of lidocaine is currently recommended in adult patients, the current recommendations regarding the use of this drug in children are still contradictory ( 35 ). In this study, we investigated the effect of adding IV lidocaine to ketamine on the hemodynamic status, endoscopist satisfaction, and patient recovery time in pediatric patients undergoing GI endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies in recent years have shown that with an appropriate dose and infusion speed, lidocaine intravenous injection will not cause serious local anesthetic toxicity. 15–17 In the present study, we chose continuous intravenous lidocaine to explore whether systemic lidocaine can reduce the incidence of POD in elderly patients. The loading dose and continuous infusion dose were determined with reference to the international consensus statement.…”
Section: Discussionmentioning
confidence: 99%